A modified analytical expression to determine the quasi-static pre-indentation loads of metal-faced sandwich beams. (June 2020) - Cagdas, Izzet U; Taskin, Melis
In this study, indentation of metal-faced and foam-cored sandwich beams under the action of quasi-static concentrated loads applied by using a flat punch is studied. First, a modified analytical expression yielding the pre-indentation load, which is based on plastic limit analysis, is developed. Then, indentation tests are conducted on specimens having extruded polystyrene core, and thin and laminated galvanized steel faces are developed to check the validity of the analytical expression. For the cases considered, the experimental results show that the analytical expression developed constitutes a lower bound to the true pre-indentation load. A parametric study is also conducted and the influences of the face sheet lamination parameters on the pre-indentation load are determined.